Risk management of progression of chronic obstructive pulmonary disease at the outpatient stage, taking into account the clinical phenotype and peculiarities of the course of the disease - T. V. Tayutina (Лечащий Врач, 2024)
Objective. The purpose of the study is to evaluate the effectiveness of using the "Program for predicting an unfavorable outcome, the development of cardiovascular complications and the effectiveness of rehabilitation measures in patients with chronic obstructive pulmonary disease (CardioRisk)" (Certificate number of state registration RU2023666935, registration date 08.08.2023) to manage the risks of COPD progression at the outpatient stage, taking into account the clinical phenotype and features of the course of the disease.Materials and methods. The analysis of the effectiveness of the use of the "Program for predicting an unfavorable outcome, the development of cardiovascular complications and the effectiveness of rehabilitation measures in patients with chronic obstructive pulmonary disease (CardioRisk)" in 150 patients with COPD who are observed on an outpatient basis at the place of residence and are registered at the dispensary for the underlying disease. To assess the effectiveness, dynamic monitoring was carried out for 12 months for patients with COPD who have a high and low risk of an unfavorable outcome of the underlying disease as a result of prognosis. The dynamics of clinical manifestations, the number of exacerbations, the tolerance of physical activity and the prognosis of survival by the value of the BODE index were analyzed.Results. In the dynamic follow-up group of patients with a low risk of an unfavorable outcome of the underlying disease, a statistically significant positive degree of cough severity was noted – by 4.07% (p = 0.007), sputum separation - by 4.72% (p = 0.024). The number of exacerbations in the first group decreased by 16.08% (p = 0.05; p = 0.02), the BODE index – by 9.3% (p = 0.003; p = 0.04), exercise tolerance increased by 3.7% (p = 0.007). In the second group, there was a statistically significant increase in the severity of dyspnea by 11.3% (p = 0.04), cough – by 14.9% (p = 0.022), sputum separation – by 27.55% (p = 0.001). The number of exacerbations significantly increased during the year – by 12.1 and 8.68% (p = 0.031; p = 0.030), respectively, the BODE index increased by 15.19% (p = 0.045), which indicated a deterioration in the prognosis in terms of survival.Conclusion. The effectiveness of using the "Program for predicting an unfavorable outcome, the development of cardiovascular complications and the effectiveness of rehabilitation measures in patients with chronic obstructive pulmonary disease (CardioRisk)" (Certificate number of state registration RU2023666935, registration date 08.08.2023) to manage the risks of COPD progression at the outpatient stage, taking into account the clinical phenotype and features of the course of the disease. The program solves the problem of optimizing the dispensary observation of patients with COPD in the provision of primary medical care, allows for a comprehensive assessment of the individual total risk of an unfavorable outcome of the underlying disease. The data obtained should be taken into account for the formation of a personal rehabilitation program for patients with mandatory lifestyle modification (quitting smoking and using alternative methods to combat smoking).